GERAKAN MENCEGAH RESISTANSI ANTIBIOTIK DENGAN PEMBENTUKAN DESA BIJAK ANTIBIOTIK - Setiabudy, M.; Budayanti, N.N.S.; Yanti, N.K.S.; Adhiputra, I.K.A.I.; Widowati, I.G.A.R.; Agustina, K.K. (Buletin Udayana Mengabdi; Vol 23 No 3 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i03.p02, 2023)
Background. Antibiotic or antimicrobe resistance is one of the health issues that threaten society. Inappropriate indications for use, untimely withdrawal, and overuse of large amounts of antimicrobials lead to this resistance. Overuse of antimicrobials also occurs in livestock, resulting in residues in products that are later consumed by humans and in waste in the environment. Prevention of antimicrobial resistance needs to be pursued in both households and the livestock sector. Objective. The establishment of the Antibiotic Wise Village (SAJAKA) aims to educate as well as increase awareness and concern of the community and farmers in using antimicrobials wisely and rationally. Methods . Guidance activities are carried out to the community and farmer groups using the discussion method. In order to celebrate the World Antimicrobial Awareness Week 2022, there was also a SAJAKA gathering night activity filled with education to the community through the media of bondres role-playing art. Results. The coaching activity was attended by 5 groups of breeders and the gathering night event was attended by 200 local villagers from various ages and backgrounds. In this activity, the coverage of the community who received information was comprehensive and a 28% increase in knowledge was obtained from the posttest. Conclusion. Sharing knowledge with ordinary people about the wise use of antimicrobials is the key to preventing antimicrobial resistance. Keywords: antibiotic, resistance, wise